Dividend Policy Pada Perusahaan Manufaktur Dengan Variabel Kontrol Firm Size - Maria Gabriela, Yanti, Syanti Dewi (Jurnal Paradigma Akuntansi, 2022)
The purpose of this study is to empirically prove the effect of board gender diversity, independent board, and foreign ownership on dividend policy with firm size as the controlling variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. Based on the predetermined criteria, 53 manufacturing companies were selected as samples in this study using purposive sampling method. The analytical method used in this study is multiple linear regression using EViews 11. The results of this study indicate that foreign ownership has a positive and significant effect on dividend policy, while gender diversity and independent boards have a positive and insignificant effect on dividend policy. Firm size as controlling variable has a significant effect on dividend policy.